2021
DOI: 10.1108/ecam-05-2021-0428
|View full text |Cite
|
Sign up to set email alerts
|

4D-printed parametric façade in architecture: prototyping a self-shaping skin using programmable two-way shape memory composite (TWSMC)

Abstract: PurposeThis study aims to present an architectural application of 4D-printed climate-adaptive kinetic architecture and parametric façade design.Design/methodology/approachThis work investigates experimental prototyping of a reversibly self-shaping façade, by integrating the parametric design approach, smart material and 4D-printing techniques. Thermo-responsive building skin modules of two-way shape memory composite (TWSMC) was designed and fabricated, combining the shape memory alloy fibers (SMFs) and 3D-prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In this study, we evaluate the test design of responsive building skin assembled with TWSMC panels [15]. An overall concept and installation image are illustrated in Figs.…”
Section: Studied Design and Parameter Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we evaluate the test design of responsive building skin assembled with TWSMC panels [15]. An overall concept and installation image are illustrated in Figs.…”
Section: Studied Design and Parameter Investigationmentioning
confidence: 99%
“…Lelieveld et al [12] experimentally suggested a bending façade panel, using a thermally-activated SMP matrix, and Li et al [13] schematically reviewed the SMP's applicability on the design of kinetic buildings. Recently, Yi and Kim [14] developed a reversible building skin module by combining SMA and SMP, and Yi [15] investigated computational design of a parametric SMP building façade.…”
Section: Introductionmentioning
confidence: 99%
“…Although 4D printing has been applied in various fields like manufacturing and medicine, its utilization in construction is still limited or in the experimental stage. However, a recent study by Hwang Yi [126] implemented 4D printing to develop a prototype of a parametric smart façade that can acquire self-shaping skin and could be significant in adaptive building design and construction. Nonetheless, 4D printing is one of the disruptive technologies in the AEC industry that will create innovative design and construction ideas and implementations in the future.…”
Section: D Printingmentioning
confidence: 99%
“…Building upon the capabilities of 3D printing, 4D printing introduces an additional dimension -time (Campbell et al, 2014;Yi and Kim, 2021;Cheng et al, 2020;Yi, 2022;Demoly et al, 2021;Tibbits, 2014). Objects produced through 4D printing are designed to transform or self-assemble in response to external stimuli, such as heat, water, or light.…”
Section: D Printing: Evolution Of Dynamic Architecture Over Timementioning
confidence: 99%